Intensive glycaemic targets in overweight and obese individuals with gestational diabetes mellitus: clinical trial protocol for the iGDM study - Scifres, Christina M; Battarbee, Ashley N; Feghali, Maisa N; Pierce, Stephanie; Edwards, Rodney K; Smith, Emily M; Guise, David; Bhamidipalli, Sruthi; Daggy, Joanne; Tuuli, Methodius G (BMJ open, 2024)
IntroductionThe prevalence of both obesity and gestational diabetes mellitus (GDM) has increased, and each is associated with adverse perinatal outcomes including fetal overgrowth, neonatal morbidity, hypertensive disorders of pregnancy and caesarean delivery. Women with GDM who are also overweight or obese have higher rates of pregnancy complications when compared with normal-weight women with GDM, which may occur in part due to suboptimal glycaemic control. The current recommendations for glycaemic targets in pregnant women with diabetes are based on limited evidence and exceed the mean fasting (70.9±7.8 mg/dL) and 1-hour postprandial (108.9±12.9 mg/dL) glucose values in pregnant individuals without diabetes. Our prior work demonstrated that the use of intensive (fasting <90 mg/dL and 1-hour postprandial <120 mg/dL) compared with standard (fasting <95 mg/dL and 1-hour postprandial <140 mg/dL) glycaemic targets resulted in improved glycaemic control without increasing the risk for hypoglycaemia in pregnant individuals with GDM, but the impact of intensive glycaemic targets on perinatal outcomes is unknown.Methods and analysisThe Intensive Glycemic Targets in Overweight and Obese Women with Gestational Diabetes Mellitus: A Multicenter Randomized Trial (iGDM Trial) is a large, pragmatic randomised clinical trial designed to investigate the impact of intensive versus standard glycaemic targets on perinatal outcomes in women with GDM who are overweight and obese. During the 5-year project period, a multidisciplinary team of investigators from five medical centres representing regions of the USA with high rates of obesity will randomise 828 overweight and obese women with GDM to either intensive or standard glycaemic targets. We will test the central hypothesis that intensive glycaemic targets will result in lower rates of neonatal composite morbidity including large for gestational age birth weight, neonatal hypoglycaemia, respiratory distress syndrome and need for phototherapy when compared with standard glycaemic targets using the intention-to-treat approach to analysis.Ethics and disseminationThe Institutional Review Board (IRB) at Indiana University School of Medicine approved this study (IRB# 11435; initial approval date 25 August 2021). We will submit the results of the trial for publication in peer-reviewed journals and presentations at international scientific meetings.Trial registration numberNCT05124808.